Implementasi Metode Analytical Hierarchy Process (Ahp) Untuk Menentukan Kinerja Pegawai Berprestasi - Sri Ipnuwati (Universitas Mitra Indonesia, 2020)
AbstractEmployee performance appraisal is an assessment process carried out to produce high quality and dedicated employees. The processing system of employee performance appraisal results in the West Onion bone staffing agency is still doing the calculations manually so it cannot produce a final score. Decision Support System (SPK) that is used in helping to support decisions is the analytical hiearchy process (AHP) method, the system development method used is the waterfall method, and the data collection method used is interview technique, literature review, and observation. made produce a decision support system that can calculate the level of employee achievement and can provide benefits in making decisions for employee performance appraisal.